6-7(8x+4)=3

Simple and best practice solution for 6-7(8x+4)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-7(8x+4)=3 equation:


Simplifying
6 + -7(8x + 4) = 3

Reorder the terms:
6 + -7(4 + 8x) = 3
6 + (4 * -7 + 8x * -7) = 3
6 + (-28 + -56x) = 3

Combine like terms: 6 + -28 = -22
-22 + -56x = 3

Solving
-22 + -56x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + -56x = 3 + 22

Combine like terms: -22 + 22 = 0
0 + -56x = 3 + 22
-56x = 3 + 22

Combine like terms: 3 + 22 = 25
-56x = 25

Divide each side by '-56'.
x = -0.4464285714

Simplifying
x = -0.4464285714

See similar equations:

| 3y-9=11y+31 | | f(2/3)=3x-4 | | x^3-x+0.1=0 | | 9(n+8)=81 | | 4/5-2=3 | | 10/11x-6/11=2 | | 4x+5y=240-6y | | 9(8y-8)-(8y+3)= | | x-6x-2x= | | 13+5x-7-4x=17 | | 5y+4.5x=-10 | | x^2+2*x+y+1=0 | | 5-2squared=6 | | x^2+2x+y+1=0 | | 2n/3=2 | | 4mn/2mn-8m | | -3/8z=9 | | x^2+kx+21=0 | | 3x-4+2x=26 | | -7x+13=-5x+9 | | 3=4x^2+3x-7 | | -3x+13=4 | | -3x-4=-4x-10 | | 2=5(x+9)+8x | | 5x-6=-x-30 | | (4z^6-2z^3+5)(z^3+27i)=0 | | -2x+18=-4x+34 | | 27/(-9) | | -9x+22+11x+21=2 | | 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 |

Equations solver categories